2013
DOI: 10.1159/000355255
|View full text |Cite
|
Sign up to set email alerts
|

Anwendung von Cardiodoron® bei Patienten mit funktionellen Herz-Kreislauf-Beschwerden und/oder Schlafstörungen - Ergebnisse einer prospektiven, nichtinterventionellen Beobachtungsstudie

Abstract: Hintergrund: Etwa 25-40% aller Herzpatienten können den funktionellen Herz-Kreislauf-Beschwerden zugeordnet werden, d.h. organische Ursachen sind nicht nachweisbar. Charakteristische Symptome sind Tachykardie, Palpitationen, Herzrhythmusstörungen, Hyperventilation, Schwindel, vasovagale Synkopen und Schlafstörungen, wobei Letztere auch für sich genommen ein Problem darstellen. Diesen Erkrankungen liegen gestörte vegetative Rhythmen zugrunde. Das Arzneimittel Cardiodoron wirkt mit den 3 Heilpflanzen Primula ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
5
0
2
Order By: Relevance
“…The oils were found to possess antioxidant activity, which were rich in long-chain hydrocarbons (23.3–36.4%), oxygenated long-chain hydrocarbons (31.5–33.8%), and oxygenated monoterpenes (14.4–6.6%), with palmitic acid being the most abundant constituent (25.5–28.7%) 26 . As of non-volatile compounds, phytochemical study revealed the presence of flavonoids such as apigenin, luteolin, scutellarein, coumarins such as aesculin and aesculetin, sesquiterpene lactones including derivatives of elemane, germacrane, eudesmane, and guaiane 1 . Watanabe et al (2014) suspected that allelopathy might facilitate the invasion success of O. acanthium , therefore bioassay-guided isolation procedure was applied using wheat seeds as test species to investigate the chemicals in the leaves, which was extracted with different solvents; the CH 2 Cl 2 extract showed the most potent phytotoxic activity, which was then further purified to yield 4 compounds, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oils were found to possess antioxidant activity, which were rich in long-chain hydrocarbons (23.3–36.4%), oxygenated long-chain hydrocarbons (31.5–33.8%), and oxygenated monoterpenes (14.4–6.6%), with palmitic acid being the most abundant constituent (25.5–28.7%) 26 . As of non-volatile compounds, phytochemical study revealed the presence of flavonoids such as apigenin, luteolin, scutellarein, coumarins such as aesculin and aesculetin, sesquiterpene lactones including derivatives of elemane, germacrane, eudesmane, and guaiane 1 . Watanabe et al (2014) suspected that allelopathy might facilitate the invasion success of O. acanthium , therefore bioassay-guided isolation procedure was applied using wheat seeds as test species to investigate the chemicals in the leaves, which was extracted with different solvents; the CH 2 Cl 2 extract showed the most potent phytotoxic activity, which was then further purified to yield 4 compounds, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Onopordum (Asteraceae) comprises 50 species that distribute in continental Europe and central and southwest of Asia 1 . Among them, O. acanthium L. , also known as Scotch thistle, is a biennial species, and height of mature plants can reach up to 3 m. Flowering plants have white lanate stems that are ridged with spiny-margined wings; the plant bears purple flowers, the inflorescence is a panicle that bears capitula 2 .…”
Section: Introductionmentioning
confidence: 99%
“…There are drops with ethanol extracts of fresh flowers of O. acanthium and P. veris and fresh herb of H. niger . These drugs are used in cardiovascular diseases and as sedative agents [14,15,16,17,18]. Gattefossé (Saint-Priest, France) has developed a cosmetic preparation containing alcohol extracts from flowers, leaves, and stems O. acanthium.…”
Section: Ethnomedical Usagementioning
confidence: 99%
“…Von September 2009 bis März 2012 dokumentierten 92 Ärzte insgesamt 522 Patienten, von denen 501 in die Auswertung eingingen und deren Daten in einem Übersichtsartikel bereits publiziert wurden [45]. Der größte Teil aller Patienten, d.h. 67% (N = 335), litt sowohl unter funktionellen Herz-Kreislauf-Beschwerden als auch unter Schlafstörungen.…”
Section: Ergebnisseunclassified